European Court of Human Rights and the Use of Force by Military Forces: An Evaluation in Light of the Right to Life - Foroogh Asadi; Hadi Salehi; Aghil Mohammadi (پژوهشنامه حقوق تطبیقی)
Article 2(1) of the European Convention on Human Rights recognizes the right to life and prohibits the deliberate deprivation of this right. However, paragraph 2 of this article addresses the use of force by law enforcement and military agents of the state in defense of individuals against unlawful violence, to effect a lawful arrest, or to prevent the escape of a lawfully detained person. Additionally, actions taken to quell a riot or insurrection that may result in the unintended death of one or more individuals are not considered violations of the right to life. The European Court of Human Rights has affirmed these three scenarios, in light of paragraph 2 of Article 15 of the Convention, and has also classified deaths resulting from lawful acts of war as exceptions to the right to life. This article employs a descriptive-analytical method to examine four specific situations and addresses the question: under what conditions is it permissible to derogate the right to life in these cases? The article concludes that, based on the interpretation of the convention and the precedents set by the European Court of Human Rights, violations of the right to life in these four situations are not absolute. Furthermore, the use of force in these cases must be both necessary and unavoidable. Several conditions must be satisfied in the stages before, during, and after the use of force. This matter reflects the court's approach to safeguarding the right to life and restricting deviations from it to very exceptional circumstances, which aligns with the provisions and underlying principles of the convention.